Estudio de implantación de una wlan sobre umts - Alvarez, Carlos (2010)
This study aimed to investigate the technology and equipment needed for the convergence of WLAN on UMTS, as well as establish the components and factors to be required in the existing cellular operators in Ecuador to build a UMTS network. The project which has been structured in 3 sections that are detailed below. Chapter 1 describes the UMTS system, both its general aspects, structure, conceptual model and architecture of the network. It also mentions the elements of the core network, the radio access network and their interfaces. Chapter 2 provides important foundations for the convergence of the wireless network WLAN and cellular networks to third generation. The main focus of this chapter is the study of UMA technology, protocols and procedures, as a means of convergence between the technologies mentione. Chapter 3 is a technical study for the implementation of a WLAN UMTS networks. This chapter presents the resources required to implement mentioned, as well as a description of the equipment that will be added to the local networks to enable the convergence of WLAN and UMTS.